RELATIONSHIP OF WORKERS’ CHARACTERISTICS AND THE USE OF PERSONAL PROTECTIVE EQUIPMENT AGAINST THE ENHANCEMENT OF C-REACTIVE PROTEIN SERUM ON KAPOK-PROCESSING INDUSTRY WORKERS AT BANDREK, PASURUAN - Fitrotuz Zahroh; Soedjajadi Keman (Universitas Airlangga, 2022)
Introduction: The cotton processing industry is an industry that produces cotton dust during the production process. Workers are at risk of exposure to cotton dust, if inhaled and accumulated in the body will cause inflammation that causes an increase in C-Reactive Protein (CRP) serum. The purpose of this research was to determine the relationship between the use of personal protective equipment and worker characteristics that can cause an increase in serum CRP of workers before and after work in the cotton processing industry. Methods: This was observational research with a prospective longitudinal design. Respondents in this study were 11 workers in Bandrek village, Mojotengah, Pasuruan. Data collection of worker characteristics was done by interview and observation. Personal dust content data was collected using a personal dust sampler (PDS) with gravimetric calculation methods. increase in CRP data collection using blood specimen collection before and after and conducted laboratory testing using i-chroma reader. Measurement of average dust levels of 5.49 mg / m3. Result: There was no significant correlation between personal dust level (p = 0.324) and the use of PPE (p= 0,925) with the increase in CRP serum levels. There was a significant correlation between the ages of workers (p = 0.005), years of service (p = 0.006), and length of work (p = 0.004) with the increase in CRP serum level. Conclusion: The older the workers, the longer the working period and the longer the working hour, the higher the increase of CRP serum level would be.